Trends in honey purchase and consumption in Trás-os-Montes Region, Portugal - Ribeiro, Maria Isabel (2019)
Honey is considered the only food of animal origin that can be consumed without being processed. The literature presents several reasons associated with the consumption of honey, namely, it is a natural and healthy product; its dietary, nutritional and medicinal characteristics; the product quality; the region of origin; the information available on the product label, the brand's reputation; as well as, the variety, texture, taste, aroma, appearance, packaging and price. Thus, this research intends to identify determinant factors on which consumers base their purchasing decision. Therefore, a cross-sectional study was developed based on a non-probabilistic sample of 474 individuals, of whom 399 were honey consumers. Data collection took place from March to May 2016 and was based on a questionnaire [1], which was applied directly to consumers in the city of Bragança. Later, data was analysed with SPSS 23.0 software. The data analysis included a univariate descriptive analysis and a multivariate analysis that involved the estimation of a binary logistic regression in order to identify the determinant factors of honey purchase and consumption. The statistically significant parameters included taste, colour, origin and certification label, at a significance level of 1%. These characteristics explained 68.9% of the consumer's decision to purchase honey. It is noteworthy that the certification label was considered important by non-honey consumers, probably when they purchase the product to offer. While taste, colour and country of origin were important characteristics that honey consumers valued in the purchasing decision process.